Leveraging Marketing Automation to Enhance Customer Relationship Management and Improve Management Performance in MSME B2B - Yanti, Pitri; Hurriyati, Ratih; Dirgantari, Puspo Dewi (PT. Riset Press International, 2024)
This study aimed to explore the impact of using marketing automation in customer relationship management strategies and ultimately improving management performance in the context of B2B Micro, Small and Medium Enterprises (MSMEs). The research method involved primary data collection using a quantitative approach and a non-probability sampling method, specifically purposive sampling, on 105 samples that actively use marketing automation tools. The analysis technique used was Structural Equation Modeling (SEM) with the help of Lisrel 8.80 software. The results show that marketing automation has a positive and significant impact on B2B customer relationship management, with reach of message as the most dominant indicator, contributing 65.61%. Furthermore, B2B customer relationship management also has a positive and significant effect on Marketing Performance, where improving the quality of customer relationships is the most dominant indicator at 77.4%, and the most dominant indicator in shaping marketing performance is having a larger market, accounting for 42.25%. The conclusion of this study is that the use of marketing automation in customer relationship management strategies can improve the marketing performance of B2B-based MSMEs.